the LANDASAN METODOLOGIS DALAM DISIPLIN FILSAFAT: SEBUAH TINJAUAN PUSTAKA SISTEMATIS - Ika Ismail Kayyis; Djedjen; Muhamad Andrian; Jenuri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
As the foundation of all branches of knowledge, philosophy is characterized by a unique and fundamental methodological approach, which distinguishes it from the empirical sciences. This study aims to explore and explain the methodological principles underlying philosophical inquiry through a systematic literature review. The method applied is library research by analyzing primary and secondary sources in the form of philosophical texts, academic journals, and reliable scientific articles. The research findings reveal that the methodology of philosophy is complex, consisting of a series of interwoven core principles. These principles include: (1) the Critical-Radical Principle, which prioritizes a skeptical attitude towards all assumptions in order to achieve a definite foundation for thought; (2) the Systematic-Coherent Principle, which requires the construction of thought that is orderly, logical, and consistent; (3) the Speculative Principle, which encourages rational exploration beyond empirical data to the realm of possibility; (4) the Conceptual-Analytical Principle, which focuses on filtering, clarifying, and interpreting fundamental terms; (5) Reflective Principle, which involves reflection on epistemological, metaphysical, and axiological foundations; and (6) Comprehensive-Universal Principle, which seeks to embrace reality holistically and pursue comprehensive truth. The discussion in this article focuses on the role of these principles not only as instruments for the work of philosophers, but also as pillars for the development of other disciplines. It is concluded that understanding the methodological principles of philosophy is essential for distinguishing the characteristics of philosophy from science and for honing high-level reasoning skills.